A study of the relationship between the academic discipline and the proportion of overdue books in selected U.P. Diliman libraries - Buce, Maricel B. (2003)
This study has been conducted to determine, primarily, the relationship between the academic discipline and the proportion of overdue books in the discipline's library. It covers the period of one semester from mid-June 2002 to mid-October, 2002 and the selected disciplines in U.P. Diliman are Engineering, Science, Mass Communication, and Public Administration and Governance.